Tree Water Uptake and Suction Distribution on Tropical Residual Soil Slope - Mohd Fakhrurrazi, Ishak; F.F., Sulaiman; N., Ali; A., Kassim (IOP Publishing Ltd., 2016)
This paper present an exploration of soil matric suction effected by water uptake via tree root at toe of slope on various condition between wet condition (high rainfall) and dry condition (prolonged no rainfall). Matric suction generated by active root tree has substantial influence soil moisture content on residual soil slope. A field monitoring was carried out to collect matric suction data at slope in two conditions; with a tree located at toe of slope and absent of a tree. The installations of instruments particularly at slope with tree at toe were placed within vicinity of the tree with certain depths and distances. The matric suction data from field monitoring was influence by the rainfall events that lead to the instability of soils slope. Analysis of soil matric suction distribution pattern indicates that the highest matric suction value was at shallower depth and proximity of tree. The matric suction profiles obtained from field monitoring are applied as an input data to develop soil matric suction contour. The effect of transpiration driven by active root zone generated matric suction on soil at vicinity of tree may create dry soil to increase soil shear strength.